Political speech and visual reading. Case study: the covers on the illegal 1-O referendum - Irala-Hortal, Pilar (Revista General de Información y Documentación, 2020)
The political situation in Catalonia and, with it, all of Spain, has already been, and continues to be, studied from different angles. One of the areas with the greatest social presence due to the speed of dissemination, and ease of manipulation or influence, is the visual communication exercised from journalism on one side, and by social networks on the other. In the context of the analysis of the phenomenon of manipulation or, in any case, of the power to influence citizen opinions through photography, this paper aims to examine a selection of the images published on the illegal referendum of October 1, 2017 in Catalonia. The main goal is to highlight and understand the importance that images acquire in a moment of political crisis and, in addition, how it is possible to manipulate public opinion without technically manipulating images or the shots.